Primary splenic lymphoma presenting with ascites - Healy, Nuala A. (PAGEPress Publications, 2011)
An 84 year-old gentleman presented with abdominal distension, anorexia and occasional epigastric pain over a four-week period. Blood parameters revealed a hypochromic microcytic anaemia. Both CT and US scan identified ascites and a mass in the left upper quadrant. An ascitic tap was performed identifying bloody ascites and the presence of reactive mesothelial cells on cytology. A subsequent laparotomy and splenectomy was performed. Histology of the resected spleen revealed a Grade 2 follicular lymphoma (Figure 2). The patient had an uneventful postoperative recovery and was well at 6 months follow up. The spleen is an organ with an important immunological function. Primary splenic involvement occurs in less than 1% of non-hodgkin’s lymphoma. Symptoms of primary splenic lymphoma (PSL) include pyrexia, weight-loss, night sweats, generalised weakness and left upper quadrant pain secondary to spleno - megaly. Ascites is a rare presenting feature of PSL. This report illustrates a case of primary splenic lymphoma which poses diagnostic challenges for the pathologist and clinician and ultimately requires definitive splenectomy to confirm a diagnosis.